Association of Human Leukocyte Antigen Class I Polymorphism with Spontaneous Clearance of Hepatitis B Surface Antigen in Qidong Han Population - Fengqin Miao; Hang Sun; Ning Pan; Jinhuan Xu; Jie Qiu; Yuqing Shen; Wei Xie; Jianqiong Zhang (Clinical and Developmental Immunology)
Aim. To investigate whether HLA class I polymorphisms could influence the clearance of hepatitis B surface antigen (HBsAg) in Qidong Han population. Methods. We genotyped HLA-A, -B, and -C loci of 448 individuals with HBV persistent infection and 140 persons with spontaneous clearance of HBsAg by polymerase chain reaction with sequencing based typing (PCR/SBT). All the individuals were unrelated males enrolled from Qidong Han population and were followed up for 10 years. Results. The frequency of HLA-A*33:03:01G was increased in persistent HBV infection group (P value is 0.028), while frequency of HLA-B*13:01:01G was increased in HBsAg clearance group (P value is 0.0004). Conclusion. These findings suggested that the host HLA class I polymorphism is an important factor in determining the outcomes of HBV infection.